Optimization of Fermented White Glutinous Rice Tape for Ethanol Content Using the Gas Chromatography Method - Patimah; Rachmawati, Siti Rahayu; Suriawati, Junie; Sentosa, Anisya Putri; Sitorus, Sarah MMR (International Journal of Natural and Health Sciences, 2024)
One of the traditional foods that have health-preserving properties is tape which can prevent an increase in cholesterol and prevent a shortage of red blood cells. Tape products are the result of the fermentation of processed raw materials that contain starch, that is, these food ingredients become simple forms such as sugar with the addition of microbes such as yeast or yeast (Saccharomyces cerevisiae) which work to break down carbohydrate foods into alcohol and carbon dioxide by settling to form compounds. namely ethanol. The test was carried out to determine the fermentation time of the ethanol content in white sticky rice tape. The test used the gas chromatography method. The location of the testing carried out at the Pharmacy and Food Analysis Campus was obtained. The results obtained for the system suitability test analysis consisted of precision, column efficiency, and accompanying factors that met the requirements. Meanwhile, the ethanol content in samples carried out continuously for five days on days I, II, III, IV, and V respectively was 2.94%; 3.03%; 3.12%; 3.14%, and 3.28%. The greatest ethanol content obtained on day V was 3.28%, and the smallest content on day I was 2.94%. So it can be concluded that the ethanol content resulting from fermentation in white sticky rice tape increases every day and the quality of the tape decreases